Preparation for endoscopic examinations in patients with diabetes and hypoglycaemia - Lewandowski, Konrad; Rydzewska, Grażyna; K. Ledwoń, Tomasz (Gastroenterology Review/Przegląd Gastroenterologiczny, 2021)
Endoscopy is a procedure used for diagnostic and therapeutic purposes, which requires proper preparation. Patients with diabetes mellitus are particularly predisposed to inadequate cleansing for endoscopy due to slowing bowel movements, dietary preparation restrictions, glucose reduction, and the resulting symptoms of hypoglycaemia. So far, no comprehensive guidelines of preparation for endoscopic examinations for patients with these metabolic disorders have been developed. Considering the number of patients who may be subjected to colonoscopy and the possible effects of suboptimal preparation for the examination, the lack of such recommendations seems to be a significant gap in the healthcare system. The article reviews the literature on the above topic.